A view of financial factors in online distance learning during the Covid-19 pandemic - Hoo, Fang Jin; Mohd Amin Mohd Noh; Mohd Faeez Ilias; Mohd Izzuddin Mohd Pisol; Annasaii Jamar; Julia Madzala; Hasrol Basir (Penerbit Universiti Kebangsaan Malaysia, 2023)
Learning remotely during the pandemic of COVID-19 can be duly challenging specifically in financial stability and it is deemed as a major contribution in the disruptive of learning engagement. The pandemic has thrown not only learners but instructors as well into a state of vulnerability in terms of financial and this serves as a major concern in the practice of Online Distant Learning (ODL). The purpose of this study is to investigate the financial aspects among learners and instructors to perform ODL activities in Higher Education Institutions (HEI) throughout the pandemic. This study adopted a quantitative method with questionnaires as the main tool for data collection. The questionnaires were developed based on several criteria and issues of financial factors surrounding online learning during the pandemic of COVID-19. This study managed to obtain feedback from 320 respondents, among them were 225 learners and 41 instructors from public HEI and 42 learners and 12 instructors from private HEI as respondents. The findings in this paper showed that financial constraints reflected that learning in this trying time is a threat to the financial capability to all learners and instructors, especially the ones that were hit hard by the COVID-19 crisis but was not the major factor that has resulted in the failure of learning via ODL. Thus, the implementation of ODL allows learning engagement to happen in the future and HEI should move towards this path to ensure the effectiveness of education to continue in developing a model or framework for teaching and learning at a distant.